Exploring the Impact of Discovery Learning and Self-Efficacy on Students' Critical Thinking Skills - Abdul Hamid Bachtiar; Nukhan Wicaksana Pribadi; Fitria Khasanah (STAI Hubbulwathan Duri, 2025)
Critical thinking is a crucial skill for academic and lifelong success, requiring educational strategies that actively engage students. The Discovery Learning model, rooted in constructivist theory, has been widely recognized for promoting higher-order thinking. This study investigates the effects of the Discovery Learning model and students’ self-efficacy on critical thinking skills, including the interaction between these variables. A quasi-experimental design was employed involving 60 first-semester students from the Indonesian Language Department. Participants were assigned to either an experimental group (Discovery Learning) or a control group (Problem-Based Learning). Self-efficacy levels were measured using a validated questionnaire, while critical thinking was assessed through a standardized test. Data were analyzed using two-way Analysis of Variance (ANOVA). The results showed that the Discovery Learning model significantly improved students’ critical thinking skills (F = 27.409, p 0.001). Self-efficacy also had a significant main effect on critical thinking performance (F = 46.780, p = 0.010). Additionally, a significant interaction was found between the instructional model and self-efficacy (F = 5.187, p = 0.027), indicating that the impact of Discovery Learning was stronger among students with higher self-efficacy. These findings highlight the combined importance of instructional strategies and learner beliefs. Discovery Learning not only enhances critical thinking but also synergizes with self-efficacy to optimize student performance. Educators are encouraged to implement learner-centered approaches that foster both cognitive skills and student confidence.